2018
DOI: 10.1159/000496104
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Assessment of Combined Effects of Glibenclamide and Losartan in Diabetic Rats

Abstract: Objective: Diabetic complications involve multiple pathological pathways, including hyperglycemia-induced oxidative stress and inflammation. Combination therapy is usually employed to improve treatment outcomes and to lower potential adverse effects. In this study, we evaluated the effects of antidiabetic and antihypertensive agents, glibenclamide (GLI) and losartan (LT), on diabetes mellitus (DM)-associated metabolic changes in rats. Materials and Methods: Streptozotocin-induced diabetic animals were orally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
(27 reference statements)
3
19
0
1
Order By: Relevance
“…For instance, El-Demerdash et al found that LT attenuates carbon tetrachlorideinduced liver fibrosis and oxidative stress [36]. Moreover, LT markedly lowered diabetic associated oxidative hepatic damages in rats in another study [37]. Likewise, we reported that LT treatment corrects the altered redox status and oxidative injuries in liver tissues of hypercholesteremic animals.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, El-Demerdash et al found that LT attenuates carbon tetrachlorideinduced liver fibrosis and oxidative stress [36]. Moreover, LT markedly lowered diabetic associated oxidative hepatic damages in rats in another study [37]. Likewise, we reported that LT treatment corrects the altered redox status and oxidative injuries in liver tissues of hypercholesteremic animals.…”
Section: Discussionsupporting
confidence: 57%
“…Experimental diabetes was induced by a single intraperitoneal injection of 60 mg/kg freshly prepared streptozotocin (STZ; Sigma-Aldrich, ST. Louis, MO, USA) in 0.1 mol/L citrate buffer (pH 4.5), while control animals received equal volume of plain citrate buffer [ 12 ]. 72 hr following STZ injection, DM was verified by estimation of fasting blood glucose levels from animal's tail vein using Accu-Check Compact-Plus glucose meter system (Roche Diagnostics, Meylan, France) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus was induced by a single intraperitoneal injection (60 mg/kg) of streptozotocin (STZ) in overnight fasted rats by dissolving it in freshly prepared 0.1 M citrate buffer, pH 4.5 as previously described (Alotaibi et al, 2019). After STZ injection, the rats received free access of dextrose solution (5%) for 24 h to avoid hypoglycemic shock.…”
Section: Diabetic Inductionmentioning
confidence: 99%